In vitro antibacterial activities of selected TB drugs in the presence of clay minerals against multidrug-resistant strain of Mycobacterium smegmatis. Issue 1 (1st January 2020) - Arthur, Patrick K.; Amarh, Vincent; Blessie, Ethel J. S.; Yeboah, Rebecca; Kankpeyeng, Benjamin W.; Nkumbaan, Samuel N.; Tiburu, Elvis K
Abstract: Healing clay is a rich source of diverse minerals. The relevance of these indigenous minerals in the improvement of antibiotic chemotherapy against prevailing bacterial pathogens is yet to be thoroughly explored. In the present study, healing clay from archaeological context was characterized and used in combination with 19 different antibacterial drugs to test their combined in vitro activity against Mycobacterium smegmatis mc 2 155 and a multidrug-resistant (MDR) Mycobacterium smegmatis strain. Among the antibiotics tested, the anti-tuberculosis drug, pyrazinamide (Pzd), showed a drastic antimycobacterial activity against Mycobacterium smegmatis mc 2 155 in the presence of 5 µg/µL of the healing clay, whereas ribosome targeted inhibitors such as gentamicin showed significant reduction in activity in the presence of the healing clay. The resistance phenotype of the MDR Mycobacterium smegmatis strain to ampicillin and isoniazid was reversed in the presence of the healing clay. The activity of the other antibiotics was either unaffected, enhanced or reduced in the presence of the healing clay. The activity of ampicillin and isoniazid against the MDR strain in the presence of the healing clay suggest that healing clay might be a useful synergy for these antibiotics against MDR Mycobacterium tuberculosis .